Visual disorders and driving ability in persons with dementia: A mini review - Papageorgiou, Eleni; Tsirelis, Daniil; Lazari, Katerina; Siokas, Vasileios; Dardiotis, Efthimios; Tsironi, Evangelia E. (Frontiers in Human Neuroscience, 2022)
Background: Impaired driving ability in patients with AD is associated with a decline in cognitive processes and a deterioration of their basic sensory visual functions. Although a variety of ocular abnormalities have been described in patients with AD, little is known about the impact of those visual disorders on their driving performance. Aim: Aim of this mini-review is to provide an update on the driving ability of patients with dementia and summarize the primary visual disorders affecting their driving behavior. Methods: Databases were screened for studies investigating dementia, associated visual abnormalities and driving ability. Results: There is consistent evidence that dementia affects driving ability. Patients with dementia present with a variety of visual disorders, such as visual acuity reduction, visual field defects, impaired contrast sensitivity, decline in color vision and age-related pathological changes, that may have a negative impact on their driving ability. However, there is a paucity in studies describing the impact of oculovisual decline on the driving ability of AD subjects. A bidirectional association between cognitive and visual impairment has been described. Conclusion: Given the bidirectional association between visual impairment and dementia, vision screening and cognitive assessment of the older driver should aim to identify at-risk individuals and employ timely strategies for treatment of both cognitive and ocular problems. Future studies should characterize the basic visual sensory status of AD patients participating in driving studies, and investigate the impact of vision abnormalities on their driving performance.